The light of the midnight stars - Rossner, Rena (Redhook, 2021)
"Deep in the Hungarian woods, the sacred magic of King Solomon lives on in his descendants. Gathering under the midnight stars, they perform small miracles and none are more gifted than the great Rabbi Isaac and his three daughters. But darkness is creeping across Europe, threatening the lives of every Jewish person in every village. Each sister will have to make an impossible choice in an effort to survive - and change the fate of their family forever"--